Heightened attention to supplementation is needed to improve the vitamin D status of breastfeeding mothers and infants when sunshine exposure is restricted. Issue 3 (19th June 2012) - Dawodu, Adekunle; Zalla, Lauren; Woo, Jessica G.; Herbers, Patricia M.; Davidson, Barbara S.; Heubi, James E.; Morrow, Ardythe L.
Abstract Although exclusively breastfed infants are at increased risk of vitamin D (vit D) deficiency if vit D supplementation is lacking and sun exposure is limited, assessment of both risk factors in the first year of life is lacking. We evaluated the contribution of vit D intake and sunlight exposure to vit D status in 120 healthy, breastfeeding mother–infant dyads, who were followed up for 1 year. Vitamin D intake and skin sunlight exposure were evaluated using questionnaires. Serum 25‐hydroxyvitamin D, parathyroid hormone (PTH) and alkaline phosphatase levels were determined post‐natally in mothers at 4 weeks and in infants at 4, 26 and 52 weeks. Vitamin D supplementation was low (<20%) and sunlight exposure was common (93%) in study infants. At 4 weeks, 17% of mothers were vit D deficient (<50 nmol L−1) and 49% were insufficient (50–<75 nmol L−1), while 18% of infants were severely vit D deficient (<25 nmol L−1) and 77% were deficient (<50 nmol L−1). At 26 weeks, winter/spring birth season and shorter duration of months of exclusive breastfeeding were protective of vit D deficiency in infants. Vitamin D deficiency in infants decreased to 12% at 52 weeks with sunlight exposure. Serum PTH levels were significantly higher in severely vit D deficient than sufficient infants. Vitamin D deficiency was widespread in early post‐partum breastfeeding mothers and infants, and declined to one in eight infants at 52 weeks due mostly to sunshine exposure. When sunlight exposure is limited or restricted, intensified vit D supplementation of breastfeeding mothers and infants is needed to improve vit D status.